Facilitators and barriers of a subscriber identity module enabled, remote blood pressure monitoring system for residents of a low-income housing: A feasibility study - Chinwe E Eze; Hilary M Mansoor; Vincent D Marshall; Antoinette B Coe; Lorraine R Buis; Reema Kadri; Karen B Farris (Digital Health)
Introduction Almost half of US adults have hypertension (HTN) and those with low-income are more likely to have worse blood pressure (BP) control. To help manage BP, recent interventions have introduced remote, or at-home, BP monitoring. Objective To assess the feasibility of a subscriber identity module (SIM)-enabled remote BP monitoring (RBPM) intervention among individuals with HTN living in low-income housing. Methods A prospective, observational cohort pilot study of 15 low-income older adult participants was conducted. RBPM was delivered through CareSimple ® , a cloud-based, SIM-enabled, remote BP cuff. Participants were asked to check their BP at least twice weekly for 4 months, and readings were monitored via a central dashboard. Feasibility and acceptability were measured by the feasibility of the intervention measure (FIM) and acceptability of the intervention measure (AIM) via survey and semi-structured interviews. Data analyses were by descriptive and paired t -test statistics, and qualitative descriptive analysis. Result Fourteen participants with an average age of 76.5 years (SD: 9.0) completed the study. The AIM and FIM mean scores at month 4 were 4.14 (SD: 0.70) and 4.27 (SD: 0.67), respectively (scale: 1–5). Facilitators of the intervention included positive perceptions of the BP device, text messaging, and the onsite champion. Barriers were BP measurement and accuracy concerns, lack of appropriate home furniture, and negative perception of text messaging. At month 4, there were non-statistically significant decreases in average systolic BP (mean difference −3.9 mm Hg), and diastolic BP (mean difference −1.4 mm Hg). Conclusion SIM-enabled BP remote monitoring with text messages was feasible and acceptable in older adult low-income housing residents with HTN.